EFFECTIVENESS OF SUMMARIZING IN TEACHING READING COMPREHENSION FOR EFL STUDENTS - Dwi Astuti Wahyu Nurhayati; Maylia Wilda Fitriana (Center of Language and Cultural Studies [CLCS], 2018)
& This problem highlighted in this study is the low of reading comprehension of the students at MTsN Pucanglaban Tulungagung that is caused by (1) the students’ difficulties to understand about meaning in the text; (2) the students’difficulties to read and spell it correctly whether in spoken form or written form.; (3) the lack of vocabulary. The research design in this study was pre-experimental research with one group pre-test post-test design. This design involves only one group by using pre-test and post-test as the instrument. The sample was VIIIA class which consists of 34 students. The result showed that the students’ mean score in teaching reading comprehension before they are taught using summary technique was 84.37. While the students’ mean score after they are taught using summary technique was 90.43. By comparing significant level in t table at 0.05, it is known that t count is bigger than t table. Summary technique can be used as an alternative teaching technique to teach reading comprehension to the students at JHS level.